Foreign Trade Activity of the Russian Federation in the Current Context - Makhmudova, Muhabbat Madievna; Koroleva, Anna Michailovna (International Journal of Economics and Financial Issues, 2016)
The article presents the main theoretical approaches to the substantiation of the state participation in the world economic relations. The main theories of country involvement into international trade are presented. The article contains the analysis of Russian foreign economic ties in the current context. State export and import behavior and trends for 2012-2015 are set forth in the paper. Changes in the foreign trade structure of the country under current transformation of international relations are discussed herein. Having analyzed the key statistical factors defining foreign trade activity of Russia, the authors drew conclusions on the current trends of international cooperation of the country, and determined perspective lines of government support for domestic producers. Keywords: export, import, foreign-trade turnover, openness of economy, foreign trade, export quota, import quota. JEL Classifications: F19, F49, F59.